Freedom, Intentionality, and Trinitarian Love in Edith Stein’s Thought—The Need for a Phenomenology–Theology Dialogue to Have a Deeper Understanding of It (2023)
The school of phenomenology went with Edith Stein all her life and became one of the guiding strings of her thought, which deepens more and more on the experience of the crucified. The Steinian idea of freedom starts from philosophy. However, it is intimately crossed by the theological (and mystical) question, since, for the author, the historical realization of the human life is possible when it participates in the divine life because God configures his own life in perfect freedom. The basic idea in Stein’s proposal on human freedom is the self-configuration of oneself in the divine image. On the other hand, when Stein asks herself, “What is freedom?” she answers, “It means the same as this: I can”. What does this answer mean? In order to understand the comprehensiveness of Ich kann and its relation to self-configuration, it is necessary to realize the foundations that support this “I can”. Therefore, the present study will consider the two essential points of support for it: the phenomenological concept of intentionality (Intentionalität), proper to Brentano’s thought and inherited from Husserl, and the human experience of the phenomenon of divine love.